Optimization Train Auxiliary Power Converters Using Fuzzy Control Techniques - Muhammad Ilias Roslin; Siti Idzura Yusuf; Norazman Abu Hassan (Progress in Engineering Application and Technology, 2025)
This research investigates fuzzy logic control (FLC) as a potential solution to improve the performance of auxiliary power converters (APCs) in electric trains, particularly during start-up, a period in which significant overshoot and undershoot may occur. In order to operate under realistic train auxiliary loads and generate a 400-volt root-mean-square (RMS) output at 50 hertz, a comparison simulation was conducted in MATLAB/Simulink with a 670-volt direct current (DC) input inverter. The results indicated that the FLC performed significantly better than a conventional PID controller. In contrast to the 15.8% overshoot and 3.45 seconds settling time that were characteristic of PID control, the FLC achieved a settling time of just 0.1 seconds and virtually no voltage overshoot, as indicated by the data. Furthermore, FLC guaranteed a more rapid and consistent control, while concurrently minimizing current overshoot to a mere 2.7%. Fuzzy logic has been demonstrated to be particularly effective in improving both energy efficiency and system stability as a consequence of these discoveries, rendering it a potentially beneficial approach for the development of future railway auxiliary power systems.